Portret Odessy w filmie Michale Boganim „Odessa... Odessa!” - Siekierska, Marta (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
This article aims to answer the question of how the City of Odessa was portrayed in the Michale Boganim's movie Odessa... Odessa! The first part deals withthe phenomenon of the City’s omnipresence in various works of art, along with factorsthat contributed to its prosperity in 19th century. The next part of the article is devotedto the movie’s composition that partially resembles a triptych, collage and musical variation devoted to specific space. Special attention was paid to the original soundtrack, the way of shooting urban landscapes and colors, which combined together contribute to the movies overall nostalgic atmosphere. In the following part, metaphors that underline the passage of time in the movie are enumerated and analyzed. Conclusions concerning Odessians' mental and spiritual exile as well as their vision of imaginary, idealized Odessa, that no longer exists are drawn in the last part.